The Transsexual's Turn: Uncanniness at Wellesley College. Issue 4 (1st October 2016) - Gozlan, Oren
ABSTRACT: A controversy over the admission of transmen into an all-women's college featured in a recent article in The New York Times, "When Women Become Men at Wellesley" (Padawer, 2014), captures the ways in which transsexuality orients discussions of identity, sociality, at-homeness, and modes of gender self-fashioning. The presence of transmen in an all-women's college also incites debates over the history of the school's identity and the challenges of colleges in transition. Rather than entering the debate of whether transmen should or should not be allowed into the college, my articlearticle addresses the terms of this debate through its arguments over the conceptualization of gender. Whereas transmen at Wellesley College bring to the fore social implications, my discussion approaches conflictive orientations to gender through a psychoanalytic lens with special attention to the fantasy structure of gender. Working with Freud's (1919) idea of the uncanny, the essay explores the question, How may the presence of transmen in an all-women's college be thought of as opening an emotional experience and as signifying for the college a transitional time between adolescence and adulthood? Is there something about a segregated community that is desirable for transitioning? In the case of an all-women's school that carries a historical legacy involving a number of transformations regarding how we approach questions of race, gender, desegregation, and the recognition of the struggle of lesbians, the article argues that the transmen's request to belong at the college is the college's historical legacy. The article concludes with the old question that Freud asked about women: What does the transman want?